2012
DOI: 10.1002/hed.23094
|View full text |Cite
|
Sign up to set email alerts
|

Transoral en bloc resection of superficial laryngeal and pharyngeal cancers

Abstract: Our transoral en bloc resection technique can be easily adopted, and it effectively maintained QOL after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…It has been reported that TLM for laryngo-pharyngeal cancer results in an excellent organ preservation rate [11,12]. However, because of the limitation of the surgical field, the tumor has to be divided into piecemeal specimens during resection of a large-size tumor [17], which may increase the potential for local recurrence. TORS is an innovative treatment option which is quickly spreading worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TLM for laryngo-pharyngeal cancer results in an excellent organ preservation rate [11,12]. However, because of the limitation of the surgical field, the tumor has to be divided into piecemeal specimens during resection of a large-size tumor [17], which may increase the potential for local recurrence. TORS is an innovative treatment option which is quickly spreading worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Straight operation field surgeries such as TOVS and TLM provide easy maneuverability in a similar manner to that of the laryngo‐microsurgery technique, while TORS allows a better view and increased precision, especially when working in less‐accessible areas . The common demerits of these techniques include the limited view and working field . TOS aims for definitive resection with minimum safety margins that may contribute to organ and function preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscope-assisted surgeries, such as TOVS, TORS, and ELPS, afford precise views that allow resection to be completed with minimal invasiveness. [4][5][6][7][8]10 Straight operation field surgeries such as TOVS and TLM provide easy maneuverability in a similar manner to that of the laryngo-microsurgery technique, 6,[8][9][10] while TORS allows a better view and increased precision, especially when working in less-accessible areas. 4 The Note: Independent significant predictive factors were tumor depth by enhanced CT in primary endpoint 1 and poorly differentiation by pathological examination in primary endpoint 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations